THE PSYCHIC FUNCTION OF MYTHS AND FAIRY TALES IN PSYCHOANALYSIS: AN ENCOUNTER BETWEEN THE UNCONSCIOUS, LANGUAGE AND CULTURE - Chagas Ramos, Rawy (Health and Society, 2025)
This article proposes an articulation between psychoanalysis and mythology, emphasizing the symbolic function of myths and fairy tales in the psychic constitution process. Based on the contributions of Freud, Jung, Lacan, Bruno Bettelheim, and Marie-Louise von Franz, it investigates how mythical and fable narratives operate as clinical and cultural tools for the elaboration of the unconscious. The text discusses myth as the language of the unconscious, analyzes fairy tales as symbolic scripts of subjectivity, and examines their relevance in psychoanalytic clinical practice, especially with children. Concepts such as shadow, desire, sublimation, identification, and projection are also addressed, highlighting the therapeutic potential of myths and tales in the construction of the self. Finally, it shows how these narrative structures promote the symbolization of psychic conflicts and contribute to individuation and subjective transformation processes.